Новые палеарктические виды рода Norellia (Diptera, Scathophagidae) - Озеров, А.Л. (Вестник зоологии, 1993)
Norellia montanopra-tensis sp. n. (Northern Osetia)—allied to N. femoralis (Lw.), differs by antennae and middle tibia colour. N. caucasica sp. n. (Northern Osetia) —closely allied to N. monta-nopratensis sp. n., differs by vibrissa position as related to the lower eye margin, femora colour, absence of VII abdominal segment pollen in female, presence of seta on pro-epimeron. N. orientalis sp. n. (Amur area. Zeya)—from closely related N. spinimanum (FI1.) differs by colour of the proepisternal setae, structure of V abdominal sternite and male genitalia. N. insularis sp. n. (Kunashir island) —mostly resembles N. siriola-tum (Mg.), differs by the presence of two black setae on the episternum, dark spot near the apex of middle and hind femora dorsal surface, structure of V abdominal sternile, male genitalia. Type material is doposited in the Zoological Museum, Moscow University.